Endocrine disruptors, obesity, and cytokines - how relevant are they to PCOS? - Šimková, M; Vítků, J; Kolátorová, L; Vrbíková, J; Vosátková, M; Včelák, J; Dušková, M (Physiological research, 2020)
As environmental and genetic components contribute to the PCOS expression, we compared levels of endocrine disruptors, steroid hormones, cytokines, and metabolic parameters in twenty healthy, nine normal-weight PCOS women, and ten obese PCOS women. Steroid hormones, bisphenols (BPA, BPS, BPF, BPAF) and parabens (methyl-, ethyl-, propyl-, butyl-, benzyl-parabens) were measured by liquid chromatography-tandem mass spectrometry. Differences between the groups were assessed using the Mann-Whitney U test. Spearman correlation coefficients were calculated for the individual parameters relationship. Significantly higher levels of BPA, anti-Müllerain hormone, lutropine, lutropine/folitropine ratio, testosterone, androstenedione, 7beta-OH-epiandrosterone, and cytokines (IL-6, VEGF, PDGF-bb), were found in normal-weight PCOS women compared to controls. Between normal-weight and obese PCOS women, there were no differences in hormonal, but in metabolic parameters. Obese PCOS women had significantly higher insulin resistance, fatty-liver index, triglycerides, cytokines (IL-2, IL-13, IFN-gamma). In healthy, but not in PCOS, women, there was a positive correlation of BPA with testosterone, SHBG with lutropine, and folitropine, while testosterone negatively correlated with SHBG. In obese women with PCOS, insulin resistance negatively correlated with SHBG and estradiol. No differences were observed in the paraben exposure. Levels of BPA were higher in PCOS women, indicating its role in the etiology. Obesity significantly worsens the symptoms.
Keywords: index tělesné hmotnosti; syndrom polycystických ovarií; estrogeny; Obesity; Česká republika; cytokiny; Testosterone; studie případů a kontrol; Polycystic Ovary Syndrome; Adult; Cytokines; endokrinní disruptory; Czech Republic; Body Mass Index; testosteron; ženské pohlaví; Endocrine Disruptors; Humans; Estrogens; obezita; dospělí; inzulinová rezistence; Female; Insulin Resistance; lidé; Case-Control Studies